Application of Hydrothermal Altered Reservoir Identification Method in Metamorphic Rock Buried Hill of Bozhong sag, Bohai Bay Basin, China - Zhu, Boyuan; Pan, Renfang; Zhang, Chaomo; Zhang, Zhansong; Shi, Wenrui (Frontiers in Earth Science, 2022)
Hydrothermal fluid is one of the factors controlling Archean buried hill reservoirs in Bozhong 19-6. However, there are no clear studies focusing on the influence of hydrothermal alteration products and their lithological characteristics on reservoirs. Through characterization of the alteration reservoir and construction of a new subtraction model of the logging-rock mechanical alteration degree, the comprehensive uses of core, thin section, and electrical imaging logging data are considered as the research objects with metamorphic and igneous rocks. Thus, the relationship between lithologies with different alteration degrees and reservoir quality is revealed. The study shows that feldspar chloritization and sericitization are the main factors controlling the hydrothermal alteration of the reservoir; the overall alteration degree of igneous rocks is high, and the overall alteration degree of metamorphic rocks is low; the reservoir with strongly altered igneous facies is prone to forming dissolution pores, with strong reservoir inhomogeneity and poor reservoir performance (alteration degree is greater than 15%); the reservoir with weakly altered metamorphic facies is prone to developing fractures and a high reservoir productivity (alteration degree is 0); The reservoirs with altered metamorphic facies are numerous in the formation, spatially diverse in type, and second in reservoir quality only to those in the weakly altered metamorphic facies (alteration degree of 0–15%). This method is expected to provide a reference for quickly finding advantageous reservoirs in the Bohai Sag.